The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1111/j.1467-842x.2000.tb00723.x
|View full text |Cite
|
Sign up to set email alerts
|

What harms do young Australians experience in alcohol-use situations?

Abstract: Objective: An insight into the alcoholrelated experiences of young students in Perth, Western Australia, with particular emphasis to alcohol-related harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 9 publications
3
16
0
Order By: Relevance
“…Our findings are similar to those from other studies worldwide; for example, in New Zealand, the most common negative consequences of alcohol among students are hangover (55%), blackouts (33%), and vomiting (21%) (4), and among students in Australia being sick (12.8%), hangovers (12.3%), and being unable to remember what happened after drinking (10.4%) (21). A study among adolescents in Thailand also indicated that the negative consequences were nausea and vomiting (46.9%), being criticized by someone (38.8%), hangover (37.8%), driving a car or motorcycle after drinking (35.4%), and missing class (32.8%) (13).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are similar to those from other studies worldwide; for example, in New Zealand, the most common negative consequences of alcohol among students are hangover (55%), blackouts (33%), and vomiting (21%) (4), and among students in Australia being sick (12.8%), hangovers (12.3%), and being unable to remember what happened after drinking (10.4%) (21). A study among adolescents in Thailand also indicated that the negative consequences were nausea and vomiting (46.9%), being criticized by someone (38.8%), hangover (37.8%), driving a car or motorcycle after drinking (35.4%), and missing class (32.8%) (13).…”
Section: Discussionsupporting
confidence: 90%
“…Living with a family seems to be a protective factor, perhaps due to parental control. Our finding is supported by a study among Australian students in which unsupervised drinkers were almost seven times more likely to experience alcohol-related harm than supervised drinkers (21). A study among adolescents in the United States showed that teenagers who are not allowed to drink in school by their parents drink less alcohol during weekends, have a lower frequency of drinking, and tend to experience fewer negative consequences than those who are allowed to drink (20).…”
Section: Discussionsupporting
confidence: 85%
“…It has also been shown 10-13 that consumption of five or more drinks on one occasion is a separate predictor for IPV involvement. This is of concern in Australia: a recent national survey indicated that more than 70% of people aged 14 years and older are current drinkers 14 and McBride et al 6 found that young Australians (14-19 year olds) are more likely to drink at hazardous or high-risk levels than any other age group, and more than 66% of young Australians drink at these high levels.…”
Section: Discussionmentioning
confidence: 99%
“…6 Consequently, study inclusion was set at 15 years of age. Cases where the primary presenting injury was soft tissue trauma, or facial fracture not including a mandible fracture, were excluded.…”
Section: Australian Dental Journalmentioning
confidence: 99%
“…Adolescents are more prone towards risk taking and sensation seeking behaviour (Steinberg, 2007). For example, young people who are aged 14 to 19 are more likely to drink at risky levels (McBride et al, 2000) than any other age group in the general population.…”
Section: Introductionmentioning
confidence: 99%